Perbedaan Polutan Penyebab Polusi Udara Dalam Ruangan Pada Negara Maju dan Berkembang: Literature Review - Tarra Zettira; Ririh Yudhastuti (Universitas Airlangga, 2022)
Background: Most people spend more time indoors, such as at home. The presence of indoor air pollution has a health impact on the occupants of the house such as the appearance of respiratory symptoms. Objectives: This study aims to analyze differences in indoor air pollution in developed and developing countries as well as in the respiratory symptoms. Methods: The method used to collect articles is literature review. Articles taken from databases such as Pubmed, SAGE Journal, Science Direct, and Scopus. Discussion: Air contaminants found in developed countries include dampness, mold, cigarette smoke, and formaldehyde. In developing countries, air contaminants found are the result of combustion from cooking. Conclusions: This study shows that the contaminants and sources of indoor air contaminants in developed and developing countries are different due to differences in home conditions.